Perspectives on Written Cameroon Literature in English - Ambanasom, S. A. (Langaa RPCIG, 2013)
In 2009, Anglophone Cameroon literature celebrated its fifty years of existence. Now at the mature age of fifty-plus, this literature has a great deal to write home about even if it still has a lot to do in its pursuit of excellence. Part of its maturity resides in the fact that although the scale of literary creativity and literary criticism is skewed in favour of the former, Anglophone Cameroon literary criticism is gradually waking up from slumber in an attempt to catch up with the rapidly expanding creativity.